Capillary leak syndrome – A life-threatening complication rarely reported in patients with typhoid fever - Muhammad Afzal; Maria Bibi; Ayesha Afzal; Sauleha Wasif; Nayab Khaliq (Journal of the Pakistan Medical Association, 2026)
A 9-years-old girl was admitted in to a peripheral hospital with a two-week history of fever and loose stools. Despite initial treatment, her condition worsened. On arrival, she was critically ill, drowsy, lethargic, febrile, Heart Rate 108/min, Respiratory Rate 34/min and Blood Pressure 90/60 mmHg, Capillary Refill time >3 seconds and had cold peripheries. Blood Culture was sent and appropriate antibiotics started. Her condition further deteriorated, with worsening level of consciousness, oedema and abdominal distension. Serum Albumin levels were low (2 g/dL). Blood culture subsequently grew extensively drug-resistant Salmonella typhi, and antibiotic therapy was changed accordingly. She developed features consistent with capillary leak syndrome, including oliguria, rising haematocrit, and worsening oedema. Hypotension and impending shock were treated with albumin transfusion and close monitoring of vital signs and urine output. After 48 hours, her BP stabilized, with improvement in consciousness, urine output and resolution of oedema. She was discharged in stable condition after 10 days of treatment. Key words: capillary leak syndrome (CLS), typhoid fever.